ANALISIS KERUSAKAN JALAN PERKERASAN LENTUR RUAS JALAN BATU SANGKAR – OMBILIN STA 5+000 – 10+200, SUMATRA BARAT - Bunga Syifa Zhafira; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2022)
The structural and functional condition of the damaged road is very influential and can result in areduced ability of the road so that it cannot provide optimal service to the road users. The decline in the optimal quality of roads occurs due to damage to road infrastructure caused by repeated high traffic volumes. According to the indicators, it can be seen from the condition of the road surface, both structural and functional conditions that have suffered damage. The purpose of this study was to find out the types of damage that occurred and what kind of handling should be done as well as the priority values for repairing damage to the Batusangkar - Ombilin road section by requiring survey data directly to the field to obtain clear data on the dimensions of the damage. The research was conducted using the Pavement Condition Index method which, according to Shahin 2004, determines the PCI value based on 3 main factors, namely the type of damage, severity, and density of damage where the PCI method is a method from the American Guidelines and Procedures for Maintenance of Air Port Pavement (1982) and the Bina Method. Marga which is a method from Indonesia which measures damage based on the Procedures for Compiling a Road Maintenance Program 1990, to get the results and the handling that must be done. This study shows the Pavement Condition Index method, the average yield obtained on the Batusangkar – Ombilin road section, the pavement condition is 50.42 Moderate (Fair) and the Bina Marga analysis, the repair priority value is in the 4-6 range, namely the road is included in the periodic maintenance program with damage. on the Batusangkar - Ombilin road section, namely longitudinal cracks, alligator cracks, patches, holes, grain release, and stripping.